(untitled) (Journal of Hama University, 2020)
The emission of letters along with their qualities is considered one of the main concerns of Quran`s interpreters. Judge, ALBedhawi played a vital role in his interetation, Known as "The lights of Revelation and the secrets of interpretation" This is the reason why I dedicated my research to shed light on ALBedhawi`s issues, and the scholars who came before and after him, in this me the dology. The emission of letters and their qualities were cited, discussed and proved to be right by ALBedhawi in order to clarify his doctrine or what he was really unique at.